Public Television in the Digital Era - Iosifidis, P. author. aut Link
XXV, 211 p.
Keywords: By looking at a range of different European Public Television (PTV) broadcasters, this book investigates the challenges that these broadcasters encounter in a competitive digital broadcasting environment and reveals the different policies and strategies that they are adopting in order to remain accountable, competitive and efficient.